Feeding Prescriptions for Captive Management of the Gharial, Gavialis gangeticus (Reptilia, Crocodilia) - Singh, L. A. K. (Indian Forester, 1983)
Management prescriptions for feeding 100 gharial in captivity from hatching upto 5 years of age are given. The prescription includes consideration of creating feeding groups, choice of food types for different age/size groups, feeding frequencies, food requirements through different ages, record maintenance and other considerations including off-feed due to disturbances from pool cleaning and handling, care of live fish and arrangement of other food when whole fish are not available for large gharial. The yearly requirement of food for 100 gharial during the first year is 564 kg, second year 2,448 kg, third year 7,410 kg, fourth year 18,030 kg and fifth year 24,030 kg.